Sharia Norms and Digital Economy Practices: A Comparative Legal Analysis of Consumer Protection and E-Payment Regulation - Ramdhani, Fajri Zulia; Lutfi, A Hashfi (UIN Sunan Kalijaga, 2025)
In contemporary Indonesia, it is a common—though not universal—practice among merchants to impose an additional charge on consumers when payments are made using the Quick Response Code Indonesian Standard (QRIS). This practice is often justified on the basis that merchants disclose the charge in advance and that consumers provide voluntary consent, a rationale frequently associated with Fatwa No. 116/DSN-MUI/IX/2017 concerning Sharia-compliant electronic money. However, this practice raises significant regulatory and consumer protection concerns within the digital payment ecosystem. This article critically examines the regulatory challenges related to QRIS-based digital payments and their implications for consumer protection through a comparative analysis of Fatwa No. 116/DSN-MUI/IX/2017 and Bank Indonesia Regulation (PBI) No. 23/6/PBI/2021. The study identifies a fundamental divergence in the regulation of the Merchant Discount Rate (MDR): while the fatwa permits the imposition of such charges provided there is full disclosure and explicit consumer consent, PBI explicitly prohibits the transfer of MDR fees to consumers. This regulatory inconsistency and normative contradiction generate misinterpretation and legal ambiguity in practice, ultimately undermining consumer trust in digital payment systems. Consequently, this study advocates for the urgent revision of the existing fatwa through the issuance of new fatwas that more explicitly safeguard consumer rights in digital transactions.